Priva lappulacea (L.) Pers. (Verbenaceae): Nova Hospedeira de Tetranychus gigas Pritchard & Baker (Acari: Tetranychidae) no Brasil - Santos, Rodrigo Souza; Moraes, Gilberto José de; Salimena, Fátima Regina Gonçalves; Ferreira, Cleidiane de Andrade (EntomoBrasilis, 2016)
An infestation of Tetranychus gigas (Acari: Tetranychidae) was observed on Priva lappulacea plants in anthropized areas in the municipality of Paraíso do Tocantins, Tocantins state, Brazil. Mites were found in large colonies mainly on the underside of the leaves. This observation confirms P. lappulacea as a new host of T. gigas in Brazil, in addition to confirming the first records of P. lappulacea and T. gigas for Tocantins state. Priva lappulacea (L.) Pers. (Verbenaceae): New Host of Tetranychus gigas Pritchard & Baker (Acari: Tetranychidae) in Brazil Resumo. Relata-se a infestação de Tetranychus gigas (Acari: Tetranychidae) em plantas de Priva lappulacea em área antropizada no município de Paraíso do Tocantins, Estado de Tocantins. Os ácaros foram observados em numerosas colônias, principalmente na face inferior das folhas. Após confirmação, registra-se, portanto uma nova planta hospedeira para T. gigas no Brasil, além do primeiro registro de P. lappulacea e de T. gigas para o Estado de Tocantins.